Epileptic Encephalopathies in Childhood: The Role of Genetic Testing - Lemke, Johannes R.; Syrbe, Steffen (Seminars in Neurology, 2015)
The epileptic encephalopathies comprise a heterogeneous group of neurodevelopmental disorders characterized by marked epileptic activity associated with developmental regression. The genetic confirmation and classification of a clinical diagnosis in an individual may provide certainty in treatment decisions, prognosis, and evaluation of seizure recurrence risks and may also prevent unnecessary diagnostic investigations. Furthermore, without genetic testing it is challenging to classify the epileptic encephalopathies based on clinical and electroencephalogram features alone.The significant gain of knowledge of the past few years associated with improvement in genetic analyses allows for precise diagnoses in an increasing number of patients. As a consequence, known encephalopathies have been associated with even broader phenotypic ranges and novel entities constantly expand the spectrum of these disorders. Accordingly, many entities of this heterogeneous spectrum escape a precise classification using current nomenclatures.
Keywords: epileptic encephalopathy; infantile epilepsy; molecular genetic testing